Hydro-physical and chemical suitability of rosewood sawdust as a hydroponic substrate under drip irrigation - Smart Idumoro Samuel; Oluwaseun Temitope Faloye; Abiodun Okunola; Adeolu Adediran; Viroon Kamchoom‬; Natdanai Sinsamutpadung (PLoS ONE, 2025)
Comprehensive characterization of hydroponic substrate is important to determine its suitability as a growing media. Therefore, the suitability hypothesis was tested by determining the rosewood sawdust substrate hydrological response at different sizes: < 0.425, 0.425-1.70 and 1.70-2.00 mm. The physical and chemical properties of the substrates were determined in the laboratory using standard procedures. Water storage and air capacity of the substrates were determined while regression models were developed for the water storage prediction with respect to the substrate sizes and pipeline distance away from the fertigation source. The highest total porosity of 75.92% was obtained for the large particle, while the lowest value of 72.57% was recorded in the finest particle and thus translated to improved moisture content and storage efficiency. The values of field capacity obtained for the coarse and fine particle were 133 and 159%, respectively. The developed regression model for the water storage produces coefficient of determination (R2) greater than 0.6 (60%), indicating a good prediction. Results showed that major nutrients required for plants growth, in the rosewood enhanced the nutrients (N, P, K, Mg, Ca) in the applied solution, and were mostly considered normal, when compared to the standard. However, the electrical conductivity of 31.2 mS cm-1 obtained in the substrate was too high, thus necessitating the need to pre-treat it for reduced electrical conductivity (EC) before use. Therefore, considering the enhancement in the nutrients solution when applied to the rosewood, the substrate is recommended for growing crops in hydroponics.
Keywords: Composting and Vermicomposting Techniques; Innovations in Aquaponics and Hydroponics Systems; Hygrothermal properties of building materials